Diagnosis of bile acid diarrhoea by fasting and postprandial measurements of fibroblast growth factor 19. Issue 12 (December 2015) - Borup, Christian; Syversen, Charlotte; Bouchelouche, Pierre; Damgaard, Morten; Graff, Jesper; Rumessen, Jüri Johannes; Munck, Lars Kristian
Abstract : Background: A deficiency in the ileal hormone fibroblast growth factor 19 (FGF19) has been described in patients with bile acid diarrhoea (BAD), but fasting FGF19 levels have insufficient diagnostic power. We assess whether single postprandial sampling of FGF19 has greater discriminative value than fasting FGF19 for detection of BAD and we evaluate the reproducibility of fasting FGF19. Materials and methods: Twenty-six patients consecutively referred to 75 Se homocholic acid retention test (SeHCAT) were included. Serum FGF19 was measured after an overnight fast and again 1 h postprandially and again in the fasting state 1 week later. Results: Nine of 26 patients had SeHCAT less than 10% and fasting FGF19 was lower [median 62 pg/ml, interquartile range (IQR): 47–67] than in the 17 diarrhoea controls with SeHCAT at least 10% (median 103 pg/ml, IQR: 77–135, P =0.006). Postprandial FGF19 in BAD patients (61 pg/ml, IQR: 48–69) was similar to fasting values ( P =0.59) and increased insignificantly in diarrhoea controls (137 pg/ml, IQR: 88–182; P =0.25). The difference in postprandial FGF19 between patients with BAD and diarrhoea controls was highly significant ( P <0.001). Conclusion: The difference in serum FGF19 between groups of patients with BAD and diarrhoea controls is amplified postprandially. Within each group, the difference between fasting and postprandial FGF19 was not statistically significant. Further investigations are warranted on stimulated FGF19 response to elucidate its role in BAD. Abstract : Supplemental Digital Content is available in the text.